Combination therapy of recalcitrant severe psoriasis with psoriatic arthritis, diabetes nephropathy, and liver cirrhosis. (20th August 2021) - Zimmer, Sebastian; Goldust, Mohamad; Bhargava, Shashank; Wegner, Joanna; Grabbe, Stephan; Staubach‐Renz, Petra
Abstract: Objective: Treatment of recalcitrant moderate‐to‐severe psoriasis can be challenging. Combination therapy of biologics and immunosuppressive agents can be a new strategy for treating therapy‐resistant cases with comorbidities, where many systemic medications are contraindicated. Case presentation: We report a case of a 62‐year‐old diabetic man with a 30‐year history of severe plaque psoriasis and psoriatic arthritis with cirrhosis and diabetic nephropathy that was treated successfully in combination with apremilast and etanercept after multiple previous unsuccessful treatment attempts. Conclusion: There are no data supporting the combination of apremilast and etanercept in the management of recalcitrant cases of moderate‐to‐severe psoriasis and multiple comorbidities including psoriatic arthritis, diabetic nephropathy, and cirrhosis. In patients who do not respond to multiple approaches for the treatment of psoriasis, combination therapy with biologic agents and new systemic medications may lead to dramatic disease control.